2018
DOI: 10.1115/1.4040916
|View full text |Cite
|
Sign up to set email alerts
|

Tool Wear of Advanced Coated Tools in Drilling of CFRP

Abstract: This paper aims to investigate the effectiveness of super-hard ceramic coatings by evaluating tool wear when drilling carbon fiber-reinforced plastics (CFRP) composite. The drilling experiments of CFRP are conducted with diamond-like carbon (DLC) coated, AlMgB14 (BAM) coated, AlCrN and Si3N4 and TiN (simply denoted as (AlCrSi/Ti)N) coated, and uncoated tungsten carbide drills. Each coating, dictated by its unique processing technique, provides unique thickness and morphology, and its physical properties, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…This can also be observed that an inclination of 30°provided highest thrust forces for both 7315 and 7325 grades. As per literature [15], better adhesion between substrate and coating materials resulted in better performance. Another reason for better performance is comparable stiffness of both substrate and coating materials.…”
Section: Effect Of Cutting Tool Materials Gradementioning
confidence: 52%
See 2 more Smart Citations
“…This can also be observed that an inclination of 30°provided highest thrust forces for both 7315 and 7325 grades. As per literature [15], better adhesion between substrate and coating materials resulted in better performance. Another reason for better performance is comparable stiffness of both substrate and coating materials.…”
Section: Effect Of Cutting Tool Materials Gradementioning
confidence: 52%
“…The possible reason of this thrust force behavior can be linked with the poor performance of 7315 grade with TiAlN coating. To support the better performance, possible reason could be better adhesion and similar stiffness between substrate and coating materials as mentioned in literature [15]. -Keeping in view that cutting lip indents CFRP laminates initially, 30°inclination angle was the most difficult among other inclinations; as a result the cutting action in this case provided higher magnitudes of the thrust forces.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Many protective coatings against wear and corrosion which may be applied for cutting tools are not considered here due to the huge variety of their types and infinite number of specific tasks; however, some general principles and tendencies were discussed, while more information is available in specialised papers and reviews [7,155,[207][208][209][210][211]. Although chemical vapour deposition and physical vapour deposition are the two main methods of protective coating fabrication, it is suggested to look deeply into thematic papers and reviews to learn about different techniques [212,213] or find details on deposition methods in research papers concerned with specific materials and structures.…”
Section: Thermal Barrier Coatingsmentioning
confidence: 99%
“…The application of advanced coating materials is of great significance for improving the hardness, thermal stability, service life, and processing efficiency of cutting tools [ 17 , 18 ]. However, the wear of coating of cemented carbide tools is a major problem in engineering [ 19 ]. The scratch test is also an effective method to evaluate the adhesion strength and wear property of hard coating.…”
Section: Introductionmentioning
confidence: 99%